High-power ultrasound pretreatment for efficient extraction of fractions enriched in pectins and antioxidants from discarded carrots (Daucus carota L.) - Idrovo Encalada, Alondra Mariela (2019)
A useful pectin-enriched fraction (PEF) extracted through high-power-ultrasound (HPUS) pretreatment and sodium carbonate was efficiently obtained from discarded carrots. Formerly, the effect of HPUS-power intensity and time (A: 40 min-2.08 W/cm 2 ; B-E: 5–20 min ≈ 10 W/cm 2 ) on carrot powder (CP) used for PEF-isolation, was investigated. Reducing carbohydrates-, cell-wall neutral sugars- (NS), uronic acids- (UA) of pectins, and protein releases increased with HPUS-energy. CP had antioxidant capacity, containing α- and β-carotene, lutein, α-tocopherol. Only HPUS B-E treatments (≈10 W/cm 2 ) were capable to produce matrix disruption, promoting polymers’ release. CP pretreated through selected E-treatment (20 min; ≈10 W/cm 2 ) followed by 0.1M-Na 2 CO 3 (1 h-stirring) extracted the whole pectin content of CP (UA = 14.0%). PEFs were orange, with co-extracted antioxidants. More substituted (1.27 NS/UA ratio) three lower molecular weights’ components of HPUS-PEF produced higher Newtonian viscosity before shear-thinning, and calcium-crosslinked gels with lower elastic modulus (G’ = 12Pa). Sustainable HPUS/Na 2 CO 3 method isolated efficiently an antioxidants-carrying PEF useful as functional food additive.